Pemodelan Endapan Nikel Laterit Wilayah Kabupaten Luwu Timur - Shadda, Aqsal Ramadhan; Aldiyansyah, Aldiyansyah (Universitas Muhammadiyah Kendari, 2026)
This study examines the modeling of laterite nickel at the Research Site in East Luwu Regency. The initial stage of mining activities is to determine the volume of laterite nickel resources. The purpose of the study is to determine the amount of data from the geological modeling of laterite nickel deposits and then validate it, conduct modeling to determine the direction and distribution of laterite nickel deposits, and to determine the total volume of laterite nickel deposits at the research site. The method used is direct observation research, namely conducting direct field research to obtain primary data needed as research data and conducting quantitative research in the form of laterite nickel deposit volume. The results of the study indicate that the volume of laterite nickel deposits at the East Luwu Regency Research Site obtained a limonite volume of approximately 7,098,938 m3 and a saprolite volume of approximately 28,785,024 m3. Based on this, the research location requires further research, namely resource and reserve estimation in order to determine the economic value of a laterite nickel deposit.